The Routledge guidebook to Gramsci's Prison notebooks - Schwarzmantel, John (The Routledge guides to the great books, 2015)
"Gramsci's Prison Notebooks are one of the most important and original sources of modern political philosophy but the Prison Notebooks present great difficulties to the reader. Not originally intended for publication, their fragmentary character and their often cryptic language can mystify readers, leading to misinterpretation of the text. The Routledge Guidebook to Gramsci's Prison Notebooks provides readers with the historical background, textual analysis and other relevant information needed for a greater understanding and appreciation of this classic text. This guidebook: - Explains the arguments presented by Gramsci in a clear and straightforward way, analysing the key concepts of the notebooks. - Situates Gramsci's ideas in the context of his own time, and in the history of political thought demonstrating the innovation and originality of the Prison Notebooks. - Provides critique and analysis of Gramsci's conceptualisation of politics and history (and culture in general), with reference to contemporary (i.e. present-day) examples where relevant. - Examines the relevance of Gramsci in the modern world and discusses why his ideas have such resonance in academic discourse Featuring historical and political examples to illustrate Gramsci's arguments, along with suggestions for further reading, this is an invaluable guide for anyone who wants to engage more fully with The Prison Notebooks"--